The Physical Education teacher’s perspective for classes in the context of the COVID-19 pandemic - Alencar Vieira, Douglas; Santos da Costa, Louise; Solano Negrão, Ângelo; Monteiro-Santos, Roseane (RENEF, 2021)
The aim of this research was to analyze the Physical Education teacher`s perspective for the return of classes during and after the COVID-19 pandemic. Specific objectives were: to investigate teacher`s views about the change on didactic classes; and discuss possibilities for distance classes in Physical education and Basic education. It was conducted a field research type, quanti-qualitative and a questionnaire was applied to data collection. The 131 participants profile are presented in the results just as their concerns about didactic activities and practical classes focused on health, discussion of political aspects, and use of technologies; the possibility of distance learning in Basic Education becoming viable; towards issues expected by educators as soon as school activities are reestablished. It is concluded that teachers should use all the skills covered in Physical Education classes. Since in the first moment of returning to school routine, they would be an important tool to their lesson plan, which seeks to enrich the content and preserve the student health.